Modern diagnostic and treatment aspects of diabetic macular edema - Alexander Viktorovich Doga; Galina Fedorovna Kachalina; Elena Konstantinovna Pedanova; Dmitriy Anatol'evich Buryakov (Сахарный диабет)
Diabetic macular oedema (DMO) is the leading cause of vision loss and disability in working-age people with diabetes mellitus. This literature review describes pathogenetic mechanisms, concepts, diagnostic techniques and capabilities of novel laser technologies in the treatment of DMO. In recent years, the role of cytokines and growth factors in retinal neurodegeneration has been actively investigated. Modern diagnostic techniques for the treatment of diabetic macular oedema, in addition to conventional techniques, include optical coherence tomography, autofluorescence and microperimetry. These techniques allow the visualization of retinal structures and its functional condition, and they can be used to detect DMO at early stages and to provide the most effective treatment. The evolution of laser technology resulted in the formation of new approaches to DMO treatment. Subthreshold micropulse laser (SML) treatment, in conjunction with conventional photocoagulation, has pronounced therapeutic effects. SML shows high selectivity towards retinal pigment epithelium while avoiding neurosensory retina injury. Owing to the chronic nature of DMO and pathogenetic mechanisms recently discovered, further elaboration of the SML technique appears to be a very promising treatment.